Establishment and epidemiological investigation of a dual fluorescent qPCR assay for Pasteurella multocida and Salmonella in yaks in the Tibetan Autonomous Prefecture of Garzê, China - Pan, Yao; Yu, Qingting; Wang, Qi; Li, Qiang; Tian, Wei; Xin, Lingxiang; Hu, Xing; Xiao, Haiyue; Liu, Yuanjie; Zhu, Luo Rong Deng; Lan, Lan; Zhu, Liangquan; et al. (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionYaks serve as a vital economic and ecological resource in high-altitude regions, but it faces significant health challenges from various pathogens. Among these, Pasteurella multocida and Salmonella are critical pathogens that contribute to severe diseases.MethodsA duplex real-time fluorescence quantitative PCR assay was developed to simultaneously detect Pasteurella multocida and Salmonella. The species-specific genes kmt1 and invA were selected as target regions for primer and probe design. Following rigorous optimization, a duplex assay was established. Recombinant plasmids were constructed to serve as standards for generating standard curves. The detection thresholds were determined using SPSS statistical analysis and receiver operating characteristic curve methods. Furthermore, the assay’s sensitivity, specificity, stability, and clinical applicability were evaluated.ResultsThe established assay demonstrated high sensitivity, with detection limits of 100 and 10 copies for pMD-kmt1 and pMD-invA, respectively. No cross-reactivity was observed with six pathogens, including Mycoplasma bovis, infectious bovine rhinotracheitis virus and others. The standard curves showed strong linearity, with coefficients of determination of 0.995 and 0.998, and amplification efficiencies of 103.37% and 103.47% for pMD-kmt1 and pMD-invA, respectively. No interference was observed between high- and low-concentration templates during simultaneous detection. The intra- and inter-assay coefficients of variation ranged from 0.23% to 1.51%. Detection thresholds were determined to be cycle threshold values of 41.5 for P. multocida and 40.0 for Salmonella. Clinical evaluation was performed on 226 samples collected from yaks in seven counties of Ganzi Prefecture, Sichuan Province, China. The single infection rates of P. multocida and Salmonella were 20.35% (46/226) and 38.50% (87/226), respectively, while the co-infection rate was 6.19% (14/226).DiscussionThis study successfully established a duplex real-time fluorescence PCR assay that enables the simultaneous detection of P. multocida and Salmonella with high sensitivity, specificity, and efficiency. The assay offers a reliable and rapid diagnostic tool that is particularly suited for clinical and epidemiological investigations in yak populations.